18F-Choline PET/CT-Positive Lytic Bone Lesions in Prostate Cancer and Accidental Myeloma Detection. (May 2016) - Florimonte, Luigia; Orunesu, Eva; Castellani, Massimo; Longari, Virgilio; Cortelezzi, Agostino
Abstract : Abstract: 18 F-choline PET/CT was performed for suspected prostate cancer relapse in a 67-year-old man with hip pain and a rapid rise in prostate-specific antigen values (1.1 ng/mL). PET imaging showed an area of increased 18 F-choline bone uptake in the right ischium. Coregistered CT images showed a lytic bone lesion. The infrequent CT appearance of a possible prostate carcinoma metastasis led to additional laboratory testing that showed a monoclonal γ-peak and to subsequent biopsy, which revealed a solitary plasmocytoma.